Experience of socio-philosophical research of post-Soviet religiosity: specificity and methodological basis - M. A. Chernetsov (Интеллект. Инновации. Инвестиции, 2022)
The article provides a methodological basis for socio-philosophical research through the acceptance of freedom. The aim of the research is to develop an algorithm for analyzing religious and metaphysical views, which allows to formulate a holistic and meaningful idea of the spiritual sphere of life in a post-secular society, including the Russian society of the post-Soviet period. The review of the main approaches to the description of the religiosity of the population, which were used by Russian authors in the study of the post-Soviet period, is given in the article. The disadvantages of these methods are pointed out: the formality of the separation on confessional grounds, attempts to unambiguously associate a person with any religious organization, the intention to reduce the description to quantitative indicators, the ability for interested parties to interpret the results in their benefit. It makes impossible for researchers to fix many essential characteristics of religiosity, such as the degree of influence of faith on social behavior, the moral development of an individual, his attitude to bearer of other views, denominations and cultures. Thus, the relevance of problem of finding new approaches to the study of religiosity is demonstrated. As an alternative, a qualitative comprehensive analysis of religious and metaphysical ideas is proposed. It based on the socio-philosophical concept of 10 degrees of freedom-independence, developed by the Doctor of Philosophical Sciences A. G. Myasnikov. The hierarchy of freedom’s degrees, where moral and religious freedom-independence occupies the 8th level, is described. The main aspects of the concept are given. The research direction of the religiosity of the population is outlined. The aspects that should be considered during the analysis are considered in detail, including the complexity and internal consistency of religious and metaphysical ideas, the area of their practical application, etc. From the viewpoint of analyzing the society’s structure, it is proposed to consider a person as a carrier of a certain type of religiosity. This term denotes a collective characteristic that includes self-identification, dogmatic, cult, moral, behavioral and other aspects of a person’s spiritual life. In conclusion, some estimates, which are based on the results of the analysis of post-Soviet religiosity based on the concept of 10 degrees of freedom-independence, are given. It is indicated that this approach allows to consider the essential aspects of a person’s religiosity, the mechanisms of its formation, and provide to determine to what extent the conditions of society and the state contribute to the comprehensive development of the individual. The conclusion is made about the high heuristic potential of the proposed methodology. It is noted that in the course of further research additional factors may be identified, the analysis of which will allow to form a more accurate and meaningful vision of religious and metaphysical ideas.